Field evaluation of the synergistic effects of neem oil with Beauveria bassiana (Hypocreales: Clavicipitaceae) and Bacillus thuringiensis var. kurstaki (Bacillales: Bacillaceae). (December 2014) - Togbé, Codjo Euloge; Zannou, Elisabeth; Gbèhounou, Gualbert; Kossou, Dansou; Huis, Arnold van
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, the synergistic effects of Beauveria bassiana (Bals.-Criv. Vuill.) (isolate Bb11) and Bacillus thuringiensis var. kurstaki (Berliner) with neem oil were evaluated in three agroecological zones in Bénin. Four bioinsecticide treatments (neem oil, neem oil and B. bassiana used separately for different target pests, neem oil mixed with B. bassiana and neem oil mixed with B. thuringiensis) were compared with a calendar-based treatment using synthetic insecticides and a control without insecticides. The bioinsecticide treatments were less effective than the calendar-based treatment at controlling cotton pests. There was no difference in yields and the number of damaged bolls in plots under treatments with the four bioinsecticide formulations, suggesting an absence of synergy between neem oil and B. bassiana and neem oil and B. thuringiensis. The numbers of natural enemies in all the bioinsecticide treatment plots and the control plots were similar and higher than those in the calendar-based treatment plots. The highest yield and profitability were obtained with the calendar-based treatment. Screening the compatibility of plant-based products and biopesticides through bioassays is essential for a successful application of their combinations in any integrated pest management strategy.